The Role of Generative AI Companions in Promoting Reading Engagement and Self-Regulation in EFL Contexts - Sagita, Mustakim; Sagita, Eva Sulastri; Syafari, Nofiana (The Indonesian Institute of Science and Technology Research, 2025)
Reading ability is a basic requirement for academic achievements and ongoing learning processes, specifically among English as a Foreign Language (EFL) students who must handle progressively challenging linguistic and intellectual demands in modern global educational frameworks. The current approaches for teaching self-regulated learning (SRL) through training programs face a significant drawback because they do not provide enough interactivity and personalized assistance that addresses individual student requirements. Advances in generative artificial intelligence (GenAI) offer a potential solution to this challenge by delivering dynamic, adaptive guidance that enhances self-regulation in reading. This study examines the impact of GenAI-enabled SRL assistance for self-regulated reading strategies and engagement of university-level EFL students, employing a quasi-experimental design with 62 Indonesian learners from two classrooms. Following a 45-minute instructional session on SRL in reading, participants engaged in a 12-week autonomous reading program using a digital platform, with the experimental group (N= 32) receiving chatbot-based SRL assistance and the control group (N= 30) engaging in independent reading without additional support. Data from pre- and post-questionnaires, platform log analyses, and semi-structured interviews indicate that the intervention significantly enhanced students' application of self-regulated learning strategies and their level of engagement in reading activities. The findings stress the effectiveness of interactive, GenAI-assisted SRL support in fostering sustained engagement and strategic reading behaviours, accentuating its potential to address longstanding gaps in EFL reading instruction.